Efficacy of Oral Azithromycin in Treatment of Uncomplicated Enteric Fever in Children - Neelam Faryad, Lubna Riaz, Hafiz Haseeb Hanif, Asfand Tariq, Mehwish Asghar, Syed Muhammad Ahmed Raza (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Enteric fever also known as (typhoid or paratyphoid fever) is a common systemic infection with increased incidence of morbidity and mortality with salmonella typhi and paratyphi. Azithromycin has shown better outcomes in children with uncomplicated disease. Objective: To determine the efficacy of Azithromycin in treatment of uncomplicated enteric fever in children. Study Design: Descriptive case series study Place and Duration of Study: Department of Pediatrics, Sir Ganga Ram Hospital Lahore, Pakistan from 21st August 2015 to 20th February 2016. Methodology: One hundred and sixty five cases were included. Patients received capsule/suspension of Azithromycin (10 mg/kg/day) OD for 7 days. Treatment was labelled as effective if both clinical and microbiological cure were observed. Results: Patients ranged between 2-12 years of age. Mean age of the patients was 6.45±2.39 year. There were 85 males (51.5%) and 80 females (48.5%) in this study. Mean duration of fever was 6.97±1.37 days. Clinical cure, microbiological cure and efficacy was 93.9%. Conclusion: Azithromycin to be effective and safe in treatment of enteric fever. We observed high cure rate of 93.9% without any serious side effects leading to the conclusion that azithromycin is an effective oral agent for treatment for enteric fever. Keywords: Enteric Fever, Azithromycin, Salmonella Typhi/Paratyphi